Investigation of marker placement schemes for determining rearfoot motion - Csontos, Christine M. (My University, 1996)
Twelve female recreational runners (mean age = 24.5 yrs.) volunteered as Ss to determine whether there were differences in the measurement of rearfoot motion when using three different marker placement schemes during conditions of slow and fast running. Measurement of rearfoot motion consisted of touchdown angle (TA), maximum pronation angle (MPA), and time to maximum pronation (TMP). Ss were filmed running on a treadmill operating at speeds of 3.58 and 2.44 m/s at a 0% grade. The film was transferred to videotape and the ARIEL (APAS) system was used to create a 2- dimensional image of each S while running. A 2-way ANOVA with repeated measures (p < .05) was used to test the hypothesis. Results of the TA indicated significant differences between Schemes 1 and 2 and Schemes 2 and 3 for both slow and fast running conditions. Results of the MPA indicated significant differences between Schemes 1 and 2 and Schemes 2 and 3 for the slow running condition, and between Schemes 2 and 3 for the fast running condition. It appeared that markers placed on the Achilles tendon and the gastrocnemius muscle changed the mechanical axis of the lower leg and significantly influenced the measurement of rearfoot motion. Markers placed exclusively on soft tissue as in Scheme 1 appeared to move equally with similar rearfoot motion measurements as when markers placed on bony landmarks were used.
Keywords: Running injuries - Prevention; Running shoes - Design; Biomechanics; Kinematics